Cushing's syndrome: Overview of clinical presentation, diagnostic tools and complications. Issue 2 (March 2020) - Barbot, Mattia; Zilio, Marialuisa; Scaroni, Carla
Abstract : Cushing's syndrome (CS) is a severe condition that results from chronic exposure to elevated circulating cortisol levels; it is a rare but potentially life-threating condition, especially when not timely diagnosed and treated. Even though the diagnosis can be straightforward in florid cases due to their typical phenotype, milder forms can be missed. Despite the availability of different screening tests, the diagnosis remains challenging as none of the available tools proved to be fully accurate. Due to the ubiquitous effect of cortisol, it is easy understandable that its excess leads to a variety of systemic complications including hypertension, metabolic syndrome, bone damages and neurocognitive impairment. This article discusses clinical presentation of CS with an eye on the most frequent cortisol-related comorbidities and discuss the main pitfalls of first- and second-line tests in endogenous hypercortisolism diagnostic workup.